Methods of impact on the recipient in the universals of the mid-Polish day (on the example of universal councils of the sejmiki wiszeńskie) - Dawidziak-Kładoczna, Małgorzata (Philology as the Ordering of Chaos: Language and Text Studies. Ad honorem Professoris Marci Cybulski, 2018)
Universal is legal acts calling the nobility to the parliament or the common movement. The creators of the universals used impulsive and rhetorical means. They are the result of values exposed in universals. In the article I discuss the most important of these values: showing respect for the recipient, patriotism, the value of the nobility, Catholicism and tradition.